Pemodelan Keputusan Graduasi Mandiri Keluarga Penerima Manfaat Program Keluarga Harapan - Ratna Yuniarti; Harmaeniza Harmaeniza (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2025)
Modeling the Independent Graduation Decision of Conditional Cash Transfer ( CCT) Beneficiary Families aims to explain the relationship between several independent variables and the dependent variable. This model is a multiple linear regression equation. In this study, we model the factors influencing the graduation decision of Conditional Cash Transfer (CCT ) beneficiaries in Pesanggrahan Village, Montong Gading District. The research method used in this study is quantitative, with data collection using a questionnaire. The results of this study indicate that internal factors include self-awareness (79.5%) and entrepreneurship (81.8%), and external factors include the influence of P2K2 activities (82.5%) and family support (79.6%). Based on the results, 86.1% of the variation in the Graduation Decision variable can be explained by variations in the four independent variables (Self-Awareness, Entrepreneurship, P2K2 Activities, and Family Support). The remaining 13.9% is explained by factors outside the research model. In this study, P2K2 activities are the most dominant factor influencing graduation decisions